Let's simplify the expression \(9\sqrt{26} - 5\sqrt{6} + 3\sqrt{54}\) step by step.
-
Simplify \(3\sqrt{54}\): \[ \sqrt{54} = \sqrt{9 \times 6} = \sqrt{9} \times \sqrt{6} = 3\sqrt{6} \] So, \[ 3\sqrt{54} = 3 \times 3\sqrt{6} = 9\sqrt{6} \]
-
Substitute back into the expression: \[ 9\sqrt{26} - 5\sqrt{6} + 9\sqrt{6} \]
-
Combine like terms: Combine \(-5\sqrt{6}\) and \(9\sqrt{6}\): \[ -5\sqrt{6} + 9\sqrt{6} = (9 - 5)\sqrt{6} = 4\sqrt{6} \]
-
Final expression: The expression now becomes: \[ 9\sqrt{26} + 4\sqrt{6} \]
Since \(9\sqrt{26}\) and \(4\sqrt{6}\) are unlike radicals, they cannot be combined further. Thus, the final simplified expression is:
\[ 9\sqrt{26} + 4\sqrt{6} \]
To answer your initial question regarding combining radicals, the correct choice is:
- Unlike radicals cannot be combined using addition and subtraction.